TOPOLOGY OPTIMIZATION DESIGN OF AN ELECTRIC EXCAVATOR FALLING OBJECT PROTECTIVE STRUCTURES - MA Chao; LU PengCheng; ZHAO YueHe; ZHANG Xing; QIU WenNing (Jixie qiangdu)
A new falling object protective structures (FOPS) was designed by a topology optimization method based on the equivalent static load method to improve the safety of the operator of an electric excavator. Firstly, the dynamic and nonlinear crush process is simplified into multiple static and nonlinear deformation processes based on equivalent displacement. Secondly, the dynamic and nonlinear topology optimization was transformed into static and nonlinear topology optimization involving multiple load cases by the weighting coefficient method. The computational cost was saved and the convergence was improved. Finally, a new FOPS based on the topology optimization result was numerically validated based on the GB/T 17771—2010. The results show that the new FOPS can meet the safety regulation without additional protective grill and the total mass of the FOPS is reduced by 49.8 kg which are positive to save the costs of procurement and operating and reduce the fuel consumption.